SOCIAL REPRESENTATIONS ELABORATED BY NURSING STUDENTS ABOUT COVID-19 PREVENTION - Marly Marques Rêgo Neta; Antonio Rosa de Sousa Neto; Ana Raquel Batista de Carvalho; Rosângela Nunes Almeida; Andréia Rodrigues Moura da Costa Valle; Maria Eliete Batista Moura; Daniela Reis Joaquim de Freitas (Universidade Federal do Paraná, 2023)
Objective: to understand the social representations elaborated by nursing students about the prevention of COVID-19. Method: exploratory-descriptive and qualitative research. Data were produced through interviews with 32 participants, conducted in the period from September 2021 to July 2022. The Study Setting was a public higher education institution, located in the northeastern region of Brazil. Data were processed using IRaMuTeQ software. Results: the genesis of the social representations of COVID-19 prevention pointed to two axes: Organization of ideas about COVID-19 prevention measures, and Efficiency, reliability and source of the information obtained. Final Considerations: the social representations showed the knowledge about the prevention measures of COVID-19, provided an opportunity to clarify the origin of the students' knowledge and the specificities they consider important. It is hoped that this study can serve as a foundation for further research and/or interventions with nursing students.